Effect of tributyrin supplementation in high‐soya bean meal diet on growth performance, body composition, intestine morphology and microbiota of juvenile yellow drum (Nibea albiflora). (12th February 2020) - Tan, Peng; Wu, Xun; Zhu, Wenliang; Lou, Bao; Chen, Ruiyi; Wang, Ligai
Abstract: Six equal‐protein and equal‐lipid diets were formulated: the fish meal (FM) diet, the soya bean meal (SBM) diet with 40% of FM protein replaced by SBM protein and tributyrin (TB) diets with 0.05% (TB0.05), 0.10% (TB0.1), 0.20% (TB0.2) and 0.40% (TB0.4) tributyrin supplemented in the SBM‐based diet. Each kind of diet was randomly fed to triplicate tanks with 20 fish per tank. Fish were fed apparent satiation twice daily for 56 days. No significant difference in weight gain rate (WGR) and feed efficiency rate (FER) was observed between fish fed the FM, TB0.1 and TB0.2 diets ( p  > .05). Muscle histidine and arginine proportion of fish fed TB0.1 diet was significantly higher than that of fish fed the SBM diet ( p  < .05). Intestine morphology results indicated that the supplementation of 0.1% tributyrin significantly improved the mucosal fold height, microvilli length and microvilli density when compared with those of fish fed the SBM diet ( p  < .05). The supplementation of dietary tributyrin suppressed the pro‐inflammatory gene expression, which may be due to the improvement of physical barrier and modification of microbial communities, such as Acinetobacter, Rhodocyclaceae, Brevundimonas, Sphingopyxis, Hydrogenophaga, Methyloversatilis and Devosia . In conclusion, dietary 0.1% tributyrin supplementation in high‐soya bean meal diet improved growth performance, flesh quality and intestinal morphology structure integrity of yellow drum.